A photocuring preparation method of titanium / hydroxyapatite composite material

By oxidizing and coating the titanium powder at high temperature, the absorbance is reduced, and the oxide layer is reduced during the sintering process, the problem of high absorbance of titanium powder in photocuring molding is solved, and the photocuring molding of composite materials is realized and Maintaining titanium properties.

CN116271208BActive Publication Date: 2025-02-18WUHAN UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310116329.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-10
Publication Date
2025-02-18
Estimated Expiration
2043-02-10

AI Technical Summary

Technical Problem

During the photocuring and forming process of titanium/hydroxyapatite composite materials, the photosensitive resin cannot cause curing due to the high absorbance of the titanium powder, and it is impossible to prepare devices with complex shapes.

Method used

By oxidizing the titanium hydride powder at high temperature, an oxide layer is formed, which reduces the absorbance of the titanium powder and reduces the oxide layer to metal titanium during the sintering process, maintaining its mechanical and biological properties.

Benefits of technology

It effectively solves the problem of photocuring difficulties caused by high absorbance of titanium powder, realizes photocuring molding of titanium/hydroxyapatite composite materials, and can prepare objects of complex shapes while maintaining the mechanical and biological properties of titanium metal.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004078756700000011
    Figure HDA0004078756700000011
  • Figure HDA0004078756700000012
    Figure HDA0004078756700000012
  • Figure HDA0004078756700000021
    Figure HDA0004078756700000021
Patent Text Reader

Abstract

The invention discloses a photocuring preparation method of a titanium / hydroxyapatite composite material. The steps are as follows: 1) subjecting titanium hydride powder to high temperature oxidation, wherein the oxidation temperature is higher than 650°C and the time is ≤5min, grinding and crushing, and sieving to obtain titanium hydride powder coated with an oxide layer; 2) adding the titanium hydride powder coated with an oxide layer and hydroxyapatite powder to an organic photosensitive resin monomer to obtain a base slurry; 3) continuing to add a photoinitiator, a dispersant and a thickener, and ball milling to obtain a printing slurry; 4) subjecting the printing slurry to 3D printing to obtain a molded part; 5) degreasing and sintering the molded part in an oxygen-free atmosphere to obtain a titanium / hydroxyapatite composite material. The invention reduces the light absorbance of titanium powder by surface oxidation coating and modification of titanium hydride powder, solves the problem that the slurry cannot be cured due to excessive absorption of initiating light, and at the same time reduces the oxidized coating layer through the self-reduction process of titanium hydride powder during sintering, while maintaining the mechanical properties and biological properties of titanium metal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the research field of biological implant materials, and in particular relates to a photocuring preparation method of a titanium / hydroxyapatite composite material. Background Art

[0002] Ideal biomedical implant materials should have good biomechanical compatibility, that is, close to the strength and density of their own tissues, good biocompatibility, no rejection reaction with the original tissues, excellent biological activity, and can promote and induce the attachment and growth of new bones. Titanium and titanium alloys have excellent mechanical properties, corrosion resistance and biocompatibility, making them widely used as medical implant materials in clinical practice, but their biological activity is not ideal, and they cannot promote the growth of new bones and induce the differentiation of osteoblasts. The combination of bone tissue formed on the titanium surface and titanium is only mechanically embedded, which cannot meet the requirements of biological activity. Hydroxyapatite is the main component of human bones and teeth. It has good biocompatibility and biological activity. It can combine with human bones and induce the growth and formation of new bones. It is an ideal hard tissue replacement material.

[0003] Titanium and titanium alloys have excellent mechanical properties, far exceeding the modulus of human bones. Hydroxyapatite has low strength and insufficient load-bearing capacity, which limits its application. Titanium / hydroxyapatite composites have the mechanical properties of titanium, and the biological activity of their surface is improved by hydroxyapatite, making them closer to the structure and function of human bones, becoming a new research hotspot in biomaterials. Common methods for preparing titanium / hydroxyapatite composites include powder sintering, SPS and other mold sintering, but it is impossible to prepare devices with complex shapes and precise structures. The advantages of photocuring technology are rapid prototyping and moldless prototyping. Based on the 3D digital model file after intelligent processing, any complex shape of physical objects can be constructed by adding materials layer by layer. However, in the process of forming titanium / hydroxyapatite composites using photocuring technology, the titanium powder is dark in color and has a strong absorption effect on the triggering light, which has the problem of not being able to trigger the curing of photosensitive resin and thus cannot be formed.

[0004] Therefore, there is an urgent need to find a method to reduce the absorbance of titanium powder during the photocuring molding process so that the photocuring slurry containing titanium metal has the ability to cure and mold while maintaining the mechanical and biological properties of metal titanium. Summary of the invention

[0005] The purpose of the present invention is to provide a photocuring preparation method for a titanium / hydroxyapatite composite material, which reduces the light absorbance of titanium powder by surface oxidation coating and modifies titanium hydride powder, solves the problem that the slurry cannot be cured due to excessive absorption of triggering light, and reduces the oxidized coating layer through the self-reduction process of titanium hydride powder during sintering, while maintaining the mechanical properties and biological properties of titanium metal.

[0006] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:

[0007] A method for preparing a titanium / hydroxyapatite composite material by photocuring is provided, comprising the following steps:

[0008] 1) subjecting titanium hydride powder to high temperature oxidation, wherein the oxidation temperature is higher than 650° C. and the oxidation holding time is ≤5 min; and after the oxidation is completed, grinding and crushing, sieving, and obtaining titanium hydride powder coated with an oxide layer;

[0009] 2) adding the titanium hydride powder and hydroxyapatite powder coated with the oxide layer obtained in step 1) into a light-shielding bottle containing an organic photosensitive resin monomer to obtain a basic slurry;

[0010] 3) adding a photoinitiator, a dispersant and a thickener to the base slurry obtained in step 2), and mixing them evenly by ball milling to obtain a printing slurry;

[0011] 4) 3D printing the printing slurry obtained in step 3) to obtain a molded part;

[0012] 5) Degreasing the molded part obtained in step 4) in an oxygen-free atmosphere, and finally sintering to obtain a titanium / hydroxyapatite composite material.

[0013] According to the above scheme, in step 1), the titanium hydride powder is oxidized at high temperature in an air atmosphere.

[0014] According to the above scheme, in step 1), the titanium hydride powder is placed in a tubular furnace or a muffle furnace for high-temperature oxidation.

[0015] According to the above scheme, in step 1), the high temperature oxidation conditions are: 700-800°C, and the oxidation holding time is 1-3 minutes.

[0016] According to the above scheme, in step 1), the sieve is 800 mesh.

[0017] According to the above scheme, in step 1), the average particle size of the titanium hydride powder is 2 to 10 μm.

[0018] According to the above scheme, in step 2), the average particle size of the hydroxyapatite powder is 2 to 4.5 μm.

[0019] According to the above scheme, in the step 2), in the titanium hydride powder and hydroxyapatite powder coated with the oxide layer, the hydroxyapatite powder accounts for 20-80% by volume, preferably 20-60%, and more preferably 30-50%.

[0020] According to the above scheme, in step 2), the organic photosensitive resin monomer is a photocurable acrylate resin monomer; preferably at least one of trimethylolpropane formal acrylate or ethoxylated trimethylolpropane triacrylate.

[0021] According to the above scheme, in step 2), the solid content of the obtained basic slurry is ≥30 vol%, preferably 30-60 vol%.

[0022] According to the above scheme, in step 3), the photoinitiator is an organic initiator that can initiate a cross-linking reaction of the photosensitive resin; preferably, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide.

[0023] According to the above scheme, in step 3), the thickener is polyethylene glycol diacrylate; and the dispersant is SP710.

[0024] According to the above scheme, in step 3), the amount of photoinitiator added is 0-10wt% of the mass of the organic photosensitive resin monomer; the amount of dispersant added is 0-10wt% of the mass of the basic slurry; and the amount of thickener added is 0-10wt% of the mass of the basic slurry.

[0025] According to the above scheme, in step 3), the rheological properties of the slurry are adjusted by adding an organic auxiliary photoinitiator, a dispersant and a thickener, so that the slurry is -1 The viscosity at the shear rate is ≤5×10 4 Pa·s. Preferably, the viscosity is ≤1×10 3 Pa·s.

[0026] According to the above scheme, in step 3), the ball milling process is: ball milling speed 200-400r / min, ball milling time 1-5h. Preferably, the ball milling speed is 300-350r / min, and the ball milling time is 3-5h.

[0027] According to the above scheme, in step 4), a curing depth test is performed to determine the 3D printing parameters.

[0028] According to the above scheme, in step 4), the printing parameters are exposure energy 100-200 mW / cm 2 , exposure time 3 to 10s; single layer thickness not less than 30μm.

[0029] According to the above scheme, in step 5), the oxygen-free condition is in vacuum or in a protective atmosphere. Preferably, the protective atmosphere is argon or helium.

[0030] According to the above scheme, in the step 5), in the sintering process, the sintering temperature is 1300° C. to 1500° C.; the sintering time is 0.5 to 3 hours; preferably, the heating rate is 5 to 10° C. / min.

[0031] The beneficial effects of the present invention are as follows:

[0032] 1. The present invention provides a method for preparing a titanium / hydroxyapatite composite material by photocuring, wherein titanium hydride is used as a titanium source, and a titanium dioxide oxide layer is coated on the surface of the titanium hydride through prior high-temperature oxidation modification, while the interior remains titanium hydride; on the one hand, the effect of the oxide layer on light (absorption, refraction, etc.) is relatively weak, and the titanium dioxide in the oxide layer can be used to reduce the absorbance, thereby effectively solving the problem of difficulty in curing and molding photosensitive resins caused by excessive absorption of light by a slurry containing titanium powder; on the other hand, in the subsequent sintering process, the internal titanium hydride decomposes to produce hydrogen to reduce the surface oxide layer to metallic titanium, completing the self-reduction process and protecting the mechanical and biological properties of metallic titanium.

[0033] 2. The present invention applies the light-curing 3D printing technology to the preparation process of titanium / hydroxyapatite composite materials through simple operation, which is conducive to the preparation of objects with precise and complex shapes. At the same time, the equipment requirements are low and there is no danger in operation, which is suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is an EDS image of the oxide layer-coated titanium hydride powder prepared in Example 1 of the present invention, and from left to right are a cross-sectional view of the oxide layer-coated titanium hydride powder, a Ti element distribution map, and an O element distribution map.

[0035] Figure 2 This is a graph showing the absorbance of titanium hydride powder coated with an oxide layer prepared under different oxidation conditions in an embodiment of the present invention.

[0036] Figure 3 The curing depths of titanium / hydroxyapatite slurries with different ratios prepared in Examples 1-4 of the present invention.

[0037] Figure 4 These are samples formed from titanium / hydroxyapatite slurries of different proportions prepared in Examples 1-4 of the present invention.

[0038] Figure 5 Cell culture test of titanium / hydroxyapatite sintered samples with different ratios prepared in Examples 1-4 of the present invention. DETAILED DESCRIPTION

[0039] The present invention will be further described below with reference to the embodiments and drawings, but is not limited thereto.

[0040] The embodiment of the present invention provides a photocuring preparation method of a titanium / hydroxyapatite composite material. The method uses trimethylolpropane formal acrylate and ethoxylated trimethylolpropane triacrylate as the main components of a photosensitive resin, selects phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide as a photoinitiator, selects polyethylene glycol diacrylate as a thickener, selects SP710 as an organic dispersant, selects titanium hydride and hydroxyapatite as inorganic raw materials, and performs surface oxidation on titanium hydride powder to obtain a powder coated with titanium dioxide on the surface, mixes the oxidized powder with hydroxyapatite powder in proportion, adds the powder to the photosensitive resin, and adds a photoinitiator, a dispersant, and a thickener, adjusts the dosage to the optimal content by testing the curing depth and fluidity, determines the printing parameters according to the curing depth and prints, degreases and sinters the molded part in a protective atmosphere such as vacuum or argon, and obtains a sample of a titanium / hydroxyapatite composite material with a complex shape.

[0041] Embodiment 1:

[0042] A method for preparing a titanium / hydroxyapatite composite material by photocuring is provided, comprising the following steps:

[0043] 1) Titanium hydride powder with a particle size of about 10 μm is spread in an alumina crucible and placed in a tube furnace. The oxidation temperature is 700°C and the oxidation holding time is 2 minutes. After the oxidation is completed, it is ground and sieved with an 800-mesh sieve. The powder particle size is about 10 μm, and titanium hydride powder with surface oxidation coating is obtained for standby use.

[0044] 2) According to the volume ratio of 20:80 of the surface oxidation-coated titanium hydride powder obtained in step 1) and the hydroxyapatite powder with a particle size of about 4.5 μm, an appropriate amount of powder raw material is weighed. The composite materials with different titanium / hydroxyapatite ratios have different osteogenic properties, and hydroxyapatite is beneficial to promote osteogenesis. According to the solid content of the basic slurry of 35 vol%, the photosensitive resin is weighed, and the resin is trimethylolpropane formal acrylate and ethoxylated trimethylolpropane triacrylate. The weighed powder raw material and the photosensitive resin are placed in a light-shielding bottle to obtain a basic slurry.

[0045] 3) Then add a photoinitiator, a dispersant and a thickener to obtain a printing slurry; wherein the mass of the photoinitiator phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide is 3wt% of the added photosensitive resin; the mass of the dispersant SP710 is 6wt% of the mass of the base slurry; the mass of the thickener is 1wt% of the mass of the base slurry; the slurry is allowed to dry for 10s. -1 The viscosity is about 6.3 Pa·s at a shear rate.

[0046] 4) Add appropriate amount of alumina grinding beads, use a ball mill to ball mill the printing slurry at 300r / min for 4h, filter out the grinding balls after ball milling, determine the printing parameters according to the curing depth and print; the light intensity is 127.23mW / cm 2 , exposure time 3s, printing layer thickness 25μm printing 2mm thick and 20mm diameter disc (such as Figure 4 ), the molded parts were degreased in argon, the degreasing conditions were: using 35 hours to increase the temperature from room temperature to 350°C, keeping it at 350°C for 1 hour, using 6 hours to increase the temperature from 350°C to 600°C, keeping it at 600°C for 1 hour, and then sintering at a temperature of 1400°C at a heating rate of 10°C / min, keeping it at that temperature for 1 hour, to obtain a titanium / hydroxyapatite composite material.

[0047] Embodiment 2:

[0048] A method for preparing a titanium / hydroxyapatite composite material by photocuring is provided, comprising the following steps:

[0049] 1) Titanium hydride powder with a particle size of about 10 μm is spread in an alumina crucible and placed in a tube furnace. The oxidation temperature is 700°C and the oxidation holding time is 2 minutes. After the oxidation is completed, it is ground and sieved with an 800-mesh sieve. The powder particle size is about 10 μm, and titanium hydride powder with surface oxidation coating is obtained for standby use.

[0050] 2) According to the volume ratio of 40:60 of the titanium hydride powder with surface oxidation coating obtained in step 1) and the hydroxyapatite powder with a particle size of about 4.5 μm, an appropriate amount of powder raw material is weighed. According to the solid content of the basic slurry of 35 vol%, the photosensitive resin is weighed, and the resin is trimethylolpropane formal acrylate and ethoxylated trimethylolpropane triacrylate. The weighed powder raw material and the photosensitive resin are placed in a light-shielding bottle to obtain a basic slurry.

[0051] 3) Then add a photoinitiator, a dispersant and a thickener to obtain a printing paste; wherein the mass of the photoinitiator phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide is 3wt% of the added photosensitive resin, the mass of the dispersant SP710 is 4.8wt% of the mass of the base paste, and the mass of the thickener is 1wt% of the mass of the base paste. The printing paste is allowed to form within 10s. -1 The viscosity is about 5.0 Pa·s at a shear rate.

[0052] 4) Add appropriate amount of alumina grinding beads, use a ball mill to ball mill the printing slurry at 300r / min for 4h, filter out the grinding balls after ball milling, determine the printing parameters according to the curing depth and print; the light intensity is 127.23mW / cm 2 , exposure time 3s, printing layer thickness 25μm printing 2mm thick and 20mm diameter disc (such as Figure 4), degrease the molded parts in argon, the degreasing conditions are: use 35h to increase the temperature from room temperature to 350℃, keep it at 350℃ for 1h, use 6h to increase the temperature from 350℃ to 600℃, keep it at 600℃ for 1h, then sinter at 1400℃ at a heating rate of 10℃ / min, and keep it at 1h.

[0053] Embodiment 3:

[0054] A method for preparing a titanium / hydroxyapatite composite material by photocuring is provided, comprising the following steps:

[0055] 1) Titanium hydride powder with a particle size of about 10 μm is spread in an alumina crucible and placed in a tube furnace. The oxidation temperature is 700°C and the oxidation holding time is 2 minutes. After the oxidation is completed, it is ground and sieved with an 800-mesh sieve. The powder particle size is about 10 μm, and titanium hydride powder with surface oxidation coating is obtained for standby use.

[0056] 2) Weigh an appropriate amount of powder raw material in a ratio of 60:40 of the surface oxidation-coated titanium hydride powder and hydroxyapatite powder with a particle size of about 4.5 μm obtained in step 1), and weigh a photosensitive resin according to a solid content of 35 vol% of the basic slurry. The resin is trimethylolpropane formal acrylate and ethoxylated trimethylolpropane triacrylate, and the weighed powder raw material and photosensitive resin are placed in a light-shielding bottle to obtain a basic slurry.

[0057] 3) Then, a photoinitiator, a dispersant and a thickener are added to obtain a printing paste; wherein the mass of the photoinitiator phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide is 2wt% of the added photosensitive resin, the mass of the dispersant SP710 is 3.8wt% of the mass of the base paste, and the mass of the thickener is 1wt% of the mass of the base paste, so that the printing paste is formed within 10s. -1 The viscosity is about 2.4 Pa·s at a shear rate.

[0058] 4) Add appropriate amount of alumina grinding balls, use a ball mill to ball mill the printing slurry at 300r / min for 4h, filter out the grinding balls after ball milling, determine the printing parameters according to the curing depth and print; wherein the light intensity is 127.23mW / cm2, the exposure time is 5s, and the printing layer thickness is 25μm to print a 2mm thick and 20mm diameter disc (such as Figure 4 ), degrease the molded parts in argon, the degreasing conditions are: use 35h to increase the temperature from room temperature to 350℃, keep it at 350℃ for 1h, use 6h to increase the temperature from 350℃ to 600℃, keep it at 600℃ for 1h, then sinter at 1400℃ at a heating rate of 10℃ / min, and keep it at 1h.

[0059] Embodiment 4:

[0060] A method for preparing a titanium / hydroxyapatite composite material by photocuring is provided, comprising the following steps:

[0061] 1) Titanium hydride powder with a particle size of about 10 μm is spread in an alumina crucible and placed in a tubular furnace. The oxidation temperature is 700°C and the oxidation holding time is 2 minutes. After the oxidation is completed, it is ground and sieved with an 800-mesh sieve to make the powder particle size about 10 μm to obtain titanium hydride powder with surface oxidation coating for standby use.

[0062] 2) According to the surface oxidation-coated titanium hydride powder obtained in step 1) and the hydroxyapatite powder with a particle size of about 4.5 μm, a proper amount of powder raw material is weighed in a ratio of 80:20 by volume, and a photosensitive resin is weighed according to the solid content of the basic slurry being 35 vol%. The resin is trimethylolpropane formal acrylate and ethoxylated trimethylolpropane triacrylate, and the weighed powder raw material and photosensitive resin are placed in a light-shielding bottle to obtain a basic slurry.

[0063] 3) Then add a photoinitiator, a dispersant and a thickener to obtain a printing paste; wherein the mass of the photoinitiator phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide is 4wt% of the added photosensitive resin, the mass of the dispersant SP710 is 1.8wt% of the mass of the base paste, and the mass of the thickener is 1wt% of the mass of the base paste. The printing paste is allowed to thicken within 10s. -1 The viscosity is about 0.5 Pa·s at a shear rate.

[0064] 4) Add appropriate amount of alumina grinding beads, use a ball mill to ball mill the printing slurry at 300r / min for 4h, filter out the grinding balls after ball milling, determine the printing parameters according to the curing depth and print; wherein the light intensity is 127.23mW / cm2, the exposure time is 8s, and the printing layer thickness is 25μm to print a 2mm thick and 20mm diameter disc (such as Figure 4 ), degrease the molded parts in argon, the degreasing conditions are: use 35h to increase the temperature from room temperature to 350℃, keep it at 350℃ for 1h, use 6h to increase the temperature from 350℃ to 600℃, keep it at 600℃ for 1h, then sinter at 1400℃ at a heating rate of 10℃ / min, and keep it at 1h.

[0065] Embodiment 5:

[0066] A method for preparing a titanium / hydroxyapatite composite material by photocuring is provided, comprising the following steps:

[0067] 1) Titanium hydride powder with a particle size of about 10 μm is spread in an alumina crucible and placed in a tubular furnace. The oxidation temperature is 700°C and the oxidation holding time is 2 minutes. After the oxidation is completed, it is ground and sieved with an 800-mesh sieve to make the powder particle size about 10 μm to obtain titanium hydride powder with surface oxidation coating for standby use.

[0068] 2) According to the volume ratio of 20:80 of the surface oxidation-coated titanium hydride powder obtained in step 1) and the hydroxyapatite powder with a particle size of about 4.5 μm, an appropriate amount of powder raw material is weighed. The composite materials with different titanium / hydroxyapatite ratios have different osteogenic properties, and hydroxyapatite is beneficial to promote osteogenesis. According to the solid content of the basic slurry of 35 vol%, the photosensitive resin is weighed, and the resin is trimethylolpropane formal acrylate and ethoxylated trimethylolpropane triacrylate. The weighed powder raw material and the photosensitive resin are placed in a light-shielding bottle to obtain a basic slurry.

[0069] 3) Then, a photoinitiator, a dispersant and a thickener are added to obtain a printing paste; wherein the mass of the photoinitiator phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide is 3wt% of the added photosensitive resin; the mass of the dispersant SP710 is 6wt% of the mass of the base paste; and the mass of the thickener is 1wt% of the mass of the base paste; so that the printing paste is heated for 10s. -1 The viscosity is about 6.3 Pa·s at a shear rate.

[0070] 4) Add appropriate amount of alumina grinding beads, use a ball mill to ball mill the printing slurry at 300r / min for 4h, filter out the grinding balls after ball milling, determine the printing parameters according to the curing depth and print; the light intensity is 127.23mW / cm 2 , exposure time 3s, printing layer thickness 25μm printing 2mm thick and 20mm diameter disc (such as Figure 4 ), degrease the molded parts in argon gas, the degreasing conditions are: heating from room temperature to 350℃ for 35h, keeping at 350℃ for 1h, heating from 350℃ to 600℃ for 6h, keeping at 600℃ for 1h, and then sintering at 1500℃ at a heating rate of 10℃ / min, keeping at 1h. Increasing the sintering temperature will also increase the density of the sample.

[0071] Embodiment 6:

[0072] A method for preparing a titanium / hydroxyapatite composite material by photocuring is provided, comprising the following steps:

[0073] 1) Titanium hydride powder with a particle size of about 10 μm is spread in an alumina crucible and placed in a tubular furnace. The oxidation temperature is 700°C and the oxidation holding time is 2 minutes. After the oxidation is completed, it is ground and sieved with an 800-mesh sieve to make the powder particle size about 10 μm to obtain titanium hydride powder with surface oxidation coating for standby use.

[0074] 2) According to step 1), a proper amount of powder raw material is weighed in a ratio of 40:60 of the surface oxidation-coated titanium hydride powder obtained by high-temperature oxidation and hydroxyapatite powder with a particle size of about 4.5 μm, and a photosensitive resin is weighed according to a solid content of the basic slurry of 35 vol%. The resin is trimethylolpropane formal acrylate and ethoxylated trimethylolpropane triacrylate, and the weighed powder raw material and photosensitive resin are placed in a light-shielding bottle to obtain a basic slurry.

[0075] 3) Then add a photoinitiator, a dispersant and a thickener to obtain a printing paste; wherein the mass of the photoinitiator phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide is 3wt% of the added photosensitive resin, the mass of the dispersant SP710 is 4.8wt% of the mass of the base paste, and the mass of the thickener is 1wt% of the mass of the base paste. The printing paste is allowed to form within 10s. -1 The viscosity is about 5.0 Pa·s at a shear rate.

[0076] 4) Add appropriate amount of alumina grinding beads, use a ball mill to ball mill the printing slurry at 300r / min for 4h, filter out the grinding balls after ball milling, determine the printing parameters according to the curing depth and print; wherein the light intensity is 127.23mW / cm2, the exposure time is 3s, and the printing layer thickness is 25μm to print a 2mm thick and 20mm diameter disc (such as Figure 4 ), the molded parts were degreased in argon, the degreasing conditions were: heating from room temperature to 350℃ for 35h, keeping at 350℃ for 1h, heating from 350℃ to 600℃ for 6h, keeping at 600℃ for 1h, and then sintering at 1500℃ at a heating rate of 10℃ / min, keeping at 1h. Increasing the sintering temperature will also increase the density of the sample.

[0077] The present invention is not limited to the above-mentioned implementation modes. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

[0078] Figure 1 This is the oxide layer on the surface of titanium hydride under the oxidation condition of 700°C / 2min in Example 1 of the present invention. It can be seen from the figure that the thickness of the oxide layer is 1-2 μm.

[0079] In order to further verify the effect of the oxide layer on the surface of titanium hydride on the absorbance of the powder, under the condition of high temperature oxidation in step 1) of Example 1, the oxidation time was changed to 0 min, 5 min and 10 min respectively, and the absorbance of the titanium hydride coated with the oxide layer obtained at different oxidation times and the original titanium hydride powder was compared; Figure 2 It can be seen that at 700°C, the longer the oxidation holding time, the smaller the absorbance of the powder, indicating that the oxide layer is indeed beneficial to reducing the absorbance.

[0080] Figure 3The curing depth of the slurries prepared with different titanium / hydroxyapatite ratios in Examples 1-4 varies with exposure time; the figure shows that under the same curing conditions, the higher the Ti content, the lower the curing depth; as the exposure time increases, the curing deepens until it reaches a peak value.

[0081] Figure 4 The 2 mm thick and 20 mm diameter discs were photocured from the slurries prepared with titanium / hydroxyapatite of different ratios in Examples 1-4, and the Ti contents from left to right were 80%, 60%, 40%, and 20%, respectively.

[0082] Figure 5 Cell culture test of titanium / hydroxyapatite sintered samples with different ratios prepared in Examples 1 to 4. As can be seen from the figure, the osteogenic performance of titanium / hydroxyapatite composite samples is better than that of pure Ti samples, and the 40% Ti content is the best.

Claims

1. A method for preparing a titanium / hydroxyapatite composite material by photocuring, characterized in that: The steps include: 1) subjecting titanium hydride powder to high temperature oxidation, wherein the oxidation temperature is higher than 650°C and the oxidation holding time is ≤5min. After the oxidation is completed, the powder is ground and sieved to obtain titanium hydride powder coated with an oxide layer; 2) adding the titanium hydride powder and hydroxyapatite powder coated with the oxide layer obtained in step 1) into a light-shielding bottle containing an organic photosensitive resin monomer to obtain a base slurry; 3) Adding photoinitiator, dispersant and thickener to the base slurry obtained in step 2), and mixing by ball milling to obtain printing slurry; 4) 3D printing the printing slurry obtained in step 3) to obtain a molded part; 5) Degreasing the molded part obtained in step 4) in an oxygen-free atmosphere, and finally sintering to obtain a titanium / hydroxyapatite composite material.

2. The preparation method according to claim 1, characterized in that: In the step 1), the high temperature oxidation conditions are: temperature 700-800° C., and oxidation holding time 1-3 min.

3. The preparation method according to claim 1, characterized in that: In the step 1), the average particle size of the titanium hydride powder is 2 to 10 μm; in the step 2), the average particle size of the hydroxyapatite powder is 2 to 4.5 μm.

4. The preparation method according to claim 1, characterized in that: In the step 2), in the titanium hydride powder and hydroxyapatite powder coated with the oxide layer, the hydroxyapatite powder accounts for 20-80% by volume.

5. The preparation method according to claim 1, characterized in that: In the step 2), the solid content of the obtained basic slurry is ≥30 vol%.

6. The preparation method according to claim 1, characterized in that: In the step 2), the organic photosensitive resin monomer is a photocurable acrylate resin monomer; In the step 3), the photoinitiator is an organic initiator that can initiate a cross-linking reaction of the photosensitive resin; the thickener is polyethylene glycol diacrylate; The dispersant is SP710.

7. The preparation method according to claim 1, characterized in that: In the step 3), the amount of the photoinitiator added is 0-10wt% of the mass of the organic photosensitive resin monomer; the amount of the dispersant added is 0-10wt% of the mass of the basic slurry; the amount of the thickener added is 0-10wt% of the mass of the basic slurry; The added amount of photoinitiator, dispersant and thickener is not 0%.

8. The preparation method according to claim 1, characterized in that: In the step 3), the ball milling process is as follows: the ball milling speed is 200-400 r / min, and the ball milling time is 1-5 h.

9. The preparation method according to claim 1, characterized in that: In step 4), the printing parameters are exposure energy 100-200 mW / cm 2 , exposure time 3~10s.

10. The preparation method according to claim 1, characterized in that: In the step 5), in the sintering process, the sintering temperature is 1300° C. to 1500° C. and the sintering time is 0.5 to 3 hours.

Citation Information

Patent Citations

  • Surface treatment method for titanium hydride

    CN105316514A

  • Additive manufacturing of metal objects

    CN108602118A